Congenital Visual Impairment and Progressive Microcephaly Due to Lysyl–Transfer Ribonucleic Acid (RNA) Synthetase (KARS) Mutations: The Expanding Phenotype of Aminoacyl–Transfer RNA Synthetase Mutations in Human Disease. (July 2015) - McMillan, Hugh J.; Humphreys, Peter; Smith, Amanda; Schwartzentruber, Jeremy; Chakraborty, Pranesh; Bulman, Dennis E.; Beaulieu, Chandree L.; ,; Majewski, Jacek; Boycott, Kym M.; Geraghty, Michael T.
Aminoacyl–transfer ribonucleic acid (RNA) synthetases (ARSs) are a group of enzymes required for the first step of protein translation. Each aminoacyl–transfer RNA synthetase links a specific amino acid to its corresponding transfer RNA component within the cytoplasm, mitochondria, or both. Mutations in ARS s have been linked to a growing number of diseases. Lysyl–transfer RNA synthetase (KARS) links the amino acid lysine to its cognate transfer RNA. We report 2 siblings with severe infantile visual loss, progressive microcephaly, developmental delay, seizures, and abnormal subcortical white matter. Exome sequencing identified mutations within the KARS gene (NM_005548.2):c.1312C>T; p.Arg438Trp and c.1573G>A; p.Glu525Lys occurring within a highly conserved region of the catalytic domain. Our patients' phenotype is remarkably similar to a phenotype recently reported in glutaminyl–transfer RNA synthetase ( QARS ), another bifunctional ARS gene. This finding expands the phenotypic spectrum associated with mutations in KARS and draws attention to aminoacyl–transfer RNA synthetase as a group of enzymes that are increasingly being implicated in human disease.